SOIL TILLAGE VARIANTS AND SULPHUR FERTILIZATION AFFECT NODULATION, N2 FIXATION AND YIELD OF BAMBARA GROUNDNUT (Vigna subterreana) IN SOUTHEAST NIGERIA - M.A.N. Anikwe; Nnamnani D.E; Ikengannyia E.E; J.C. Eze; Obidike-Ugwu; E. O (Journal CleanWAS)
Management efficiency can increase crop productivity through enhanced N2 fixation in the plant-soil system. This study examined soil tillage variants and sulphur fertilization effects on nodulation, N2 fixation effectiveness and yield of Bambara groundnut [Vigna subterranea] in a degraded Ultisol in Agbani Enugu, Southeast Nigeria. Twenty-four experimental units were laid out in a Randomized Complete Block Design (RCBD). The six treatments comprised No-Till+No Gypsum (NTGo), No-Till+Gypsum1 (NTG1), No-Till+Gypsum2 (NTG2), Till+No Gypsum (TGo), Till+Gypsum1 (TG1), and Till+Gypsum2 (TG2). No-till+gypsum2 plots had significantly higher soil N content than each corresponding No-till+no gypsum plot by 15-40 %. At 30 DAP, the plots treated with till+gypsum1 (21 kg/ha), till+gypsum2 (42 kg/ha), no-till+gypsum2 (42 kg/ha), no-till+gypsum1 (21 kg/ha), and till+no gypsum had 62-63 % higher soil sulphur content (P= 0.05) than the control plots. The nodule count per plant in plots treated with no-till+gypsum2 (42 kg/ha) was greater than that in the control plot, plots with no-till+gypsum1 (21 kg/ha), and plots with till+gypsum2 (42 kg/ha) by 72-74 % at 30, 60, and 90 DAP across two seasons. Compared to the untreated plots, nodulation effectivity was raised by 79-89 % in the No-till+gypsum2 plot. The plots treated with no-till+gypsum2 (42 kg/ha) had the highest yield (0.94 t/ha), followed by plots treated with no-till+gypsum1 (42 kg/ha) with 0.93 t/ha dry seed yield and till+gypsum2 (42 kg/ha) with 54-55 % greater yield (P=0.05) than the control plot. Sulphur treatment boosted nodulation by 68 % and nodule effectiveness by about 78 %. The no-till+Gypsum2 application enhanced the average yield of Bambara groundnuts by 56 %. The soil application of S enhanced the amount of accessible S in the soil. Results show that the tillage system and S fertilization impact Bambara groundnut on degraded Ultisols. Dry matter yield was best with a high S supply in both S increments and no-till systems. The number and effectiveness of nodules increased at different S rates and no-tillage. Because of the increased S application rate, there was a considerable increase in N accumulation due to a greater N2 fixation rate. The study recommends using no-till systems and sulphur fertilization practices to enhance crop productivity, especially in degraded Ultisols. The study provides valuable insights into sustainable agriculture practices that boost yields while conserving soils.